MIRAGRODEP 1.0: Documentation - Laborde Debucquet, David; Robichaud, Veronique; Tokgoz, Simla (International Food Policy Research Institute, 2013)
MIRAGRODEP is a recursive-dynamic, multi-region, multi-sector computable general equilibrium model, devoted to trade and agricultural policy analysis. It is developed for AGRODEP and draws upon the MIRAGE model built by CEPII. It incorporates specific features such as foreign direct investment and runs with a tariff aggregation module that allows the user to capture the exclusion effects at a detailed level and the variance of tariffs. The model also includes a submodule allowing to test different closures for the public sector as well as the inefficiency of the tax collection system. Social Accounting Matrix (SAM) and trade data in MIRAGRODEP are based on the GTAP database. Additional sources such as MacMap are used for protection data.